BS index: incorporating R&D subsidies into B index - Zegarowicz, Łukasz (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The B index is a measure of the generosity of R&D tax incentives proposed by Warda in 2001 and is now widely used by the OECD. The author of this index already in 2001 indicated that developing it with measures of the availability of direct subsidies would improve the B index as a comprehensive measure of the attractiveness of R&D policies. Aim: Extension of the B index, used by the OECD to measure the impact of tax incentives on the conditions of investing in R&D, to include direct funding, i.e. subsidies and grants. Results: The study proposes several methods of including direct funding in the B index calculation. They depend on specific rules on which it is possible to combine the benefits of using tax incentives and direct subsidies in different countries: mutually exclusive in their use, grant funding reduces base of R&D tax credit/allowance, grant funding is part of taxable income, ceiling on total support (direct and tax), complementary in their use. The share of subsidies and direct grants in BERD in each country, broken down into SMEs and large enterprises, was adopted as the measure representing direct funding. The results show an increase in the expected subsidy rate in most of the surveyed countries in 2017. Increase is on average higher in the case of SMEs than in the case of large enterprises. The developed methods can be used for comprehensive in-depth analyzes and comparisons of R&D support policies applied in different countries. And after extending the calculations to historical data, they can be used as an important source material in modeling the impact of R&D support policies on R&D inputs and outputs.